1009. Venous 1: A Prospective Multicenter Cohort Study of Enterococcal Bacteremia. (26th November 2018) - Contreras, German; Munita, Jose M; Reyes, Katherine C; Sahasrabhojane, Pranoti; Misikir, Helina; Garza, Heather; Zervos, Marcus J; Aitken, Samuel L; Shelburne, Samuel A; Arias, Cesar
Abstract: Background: Enterococci often cause hospital-associated bloodstream infections in critically ill and immunocompromised patients. Prospective studies to assess the clinical impact of enterococcal bacteremia (EB) are lacking. We conducted a prospective study to investigate the clinical and microbiological factors associated with mortality in EB. Methods: Adults with EB were prospectively followed in three US tertiary hospitals from September 2016 to March 2018. Individuals with EB for whom follow-up blood culture data within 7 days of index culture were available were included. Microbiologic failure (MF) was defined as clearance of bacteremia ≥4 days after the first blood culture. The main outcome was hospital mortality. Results: A total of 282 patients were included with 69 (24%) infected with vancomycin-resistant enterococci (VRE). The majority of patients were male (60%) with a median age of 63 years. Median length of hospitalization for VRE patients was longer (25 d) than non-VRE (13 days, P < 0.001). E. faecium corresponded to 77% of VRE isolates, whereas E. faecalis comprised 72% of non-VRE. The average time to first blood culture was 16 days for VRE vs. 4 days for non-VRE ( P < 0.001). Patients with VRE were more likely to have hematological malignancy or bone marrow transplant ( P < 0.003), whereas patients infected non-VRE were more likely to have solid tumors ( P = 0.02). The most common antibiotic used was daptomycin as monotherapy for both VRE and non-VRE with a median dose of 8 mg/kg for both groups. Overall mortality was 25% (43% vs. 20% in VRE vs. non-VRE patients, respectively; P < 0.0001). Factors significantly associated with mortality in univariate analyses included ICU admission, prolonged hospitalization, hematological malignancy, use of immunosuppressive therapy, hemodialysis, neutropenia (<500 cell/mL), Pitt bacteremia score >3, infection with VRE and MF. ICU admission (RR 3.3; 95% CI 1.7–7.5, neutropenia (RR 4.1; 95% CI 1.3–12.9), Pitt bacteremia score >3 (RR 6.8; 95% CI 2.6–18.0), MF (RR 4.7; 95% CI 2.2–10.3) and infection with VRE (RR 4.1; 95% CI 1.1–16.6) remained significantly associated with mortality in multivariate analyses. Conclusion: The presence of VRE in EB and MF are associated with increased mortality. EB represent a major burden of disease in hospital settings. Disclosures: C. Arias, Merck & Co., Inc.: Grant Investigator, Research support. MeMed: Grant Investigator, Research support. Allergan: Grant Investigator, Research support.